Nuances of the psychogastroenterology patient: A predictive model for gastrointestinal quality of life improvement. Issue 9 (17th June 2019) - Riehl, Megan E.; Kinnucan, Jami A.; Chey, William D.; Stidham, Ryan W.
Abstract: Background: Gastrointestinal conditions are multifactorial in nature, and certain patients can benefit greatly from brain–gut psychotherapies delivered by mental health professionals who specialize in psychogastroenterology. This study aimed to identify features associated with improvements in GI‐specific quality of life scores following behavioral health interventions (BHI). The second aim was to create a psychogastroenterology referral care pathway incorporating identified characteristics for greatest benefit from GI‐specific behavioral therapy. Methods: We performed a prospective observational study of 101 (63 women; median age, 45 years) gastroenterology patients referred for psychogastroenterology consultation at a single center. Patients attended an average of seven sessions with a single GI psychologist where evidence‐based brain–gut psychotherapies were employed. GI‐specific quality of life (IBS‐QOL) and psychological distress (BSI‐18) were assessed before and after BHI. Patients completed self‐reported questionnaires. We performed a multivariable analysis to determine predictors associated with IBS‐QOL score improvement. Key Results: A total of 53 (52.5%) patients experienced improvement in IBS‐QOL score. Patients with improved IBS‐QOL scores had significantly higher baseline BSI general domain T‐scores (61.9 vs. 56.9, P  = 0.002). Female gender (odds ratio [OR], 3.2), pretreatment BSI somatization T‐score ≥63 (OR, 3.7), and a diagnosis of depression (OR, 4.2) were associated with greater odds of IBS‐QOL score improvement following BHI. Conclusions and Inferences: We identified factors associated with response to GI‐specific BHI to aid in optimizing the utilization of psychogastroenterology services and provide referring providers with information to inform treatment recommendations. Female patients with disorders of gut–brain interaction (DGBIs), high somatization, and depression should be considered a priority for brain–gut psychotherapies. Abstract : Gastrointestinal conditions are multifactorial in nature, and certain patients can benefit greatly from brain–gut psychotherapies delivered by mental health professionals who specialize in psychogastroenterology. Females with disorders of gut–brain interaction, high somatization, and depression should be considered priority for brain–gut psychotherapies. Behavioral health outcomes were not limited to disease; patients with IBD should be routinely considered for referral. Optimizing utilization of GI‐specific behavioral health specialists for the best outcomes can maximize quality of life and disease experience, but also improve value‐based care.